The Effect of Basic Life Support (BLS) Training in The Knowledge and Skill Level of Community in Sidodadi Village, Lawang, Indonesia - Maria Arni Stella; Prima Hapsari Wulandari; Tantri Adhiatama Lukitaningrum Subianto; Farah Adiba Binti Mohamad Jahari; Aida Nur Aisyah; Isna Mahmudah; Steven Sandjaja; Septian Dwi Prabowo; Djohar Nuswantoro; Heri S Widodo (Indonesian Journal of Anesthesiology and Reanimation, 2020)
Introduction: About 300.000 – 350.000 Indonesian people suffer from cardiac arrest each year. Basic Life Support (BLS) is the first immediate response needed by cardiac arrest people, especially the out of hospital cardiac arrest (OHCA) patient. BLS that given from public to OHCA could increase the survival rate up to 2 – 3x higher. Unfortunately, the Indonesian still did not know what is cardiac arrest, how to recognize it, and how to do BLS. Objective: The objective of this study was to identify the effect of BLS training in the knowledge and skill level of community in Sidodadi Village, Lawang, Indonesia. Method and Material: This experiment used a quasi-experimental design with 102 of the random sampling of people age 20-40 in Sidodadi Village, Lawang, Indonesia. The sample was given pre-test and post-test knowledge questioner before and after joining BLS training. The sample's skill was scored by an assistant doctor using a skill checklist. The data then analysed with a t-paired sample test, Wilcoxon sum rank test, and Pearson correlation. Result and Discussion: The score of women is higher than men both in pre-test and post-test, with the significance of p=0,039 for pre-test and p=0,001. 99% who joined BLS training have a significant increase in knowledge with p=0,001. Conclusion: The increase in knowledge and skill is correlated for an excellent and good level of the score, but not correlated in a bad level. About 99% of people who have joined BLS training have a significant increase in knowledge and skill. These trained people have the willingness to be a bystander for cardiac arrest people near them.